A metamaterial-free omnidirectional invisibility cloak based on thrice transformations inside optic-null medium. (January 2023) - Liu, Yichao; Sun, Fei; Yang, Yibiao; Hao, Yuying; Liang, Shaowei; Wang, Zheng
Highlights: Using higher transformations inside the ONM to make design. Regardless of the shape of the concealed region, the material parameters of the designed cloak remain unchanged. Can be realized by only natural materials, i.e., metallic channels filled with dielectrics, whose refractive indices take a range determined only by the size of the cloak. Nearly perfect invisibility effect for any type of detecting wave incident from any angle. Abstract: A full space omnidirectional cloak with an optic-null medium (ONM) shell and an isotropic homogeneous restoring core is designed by thrice coordinate transformations inside ONM. The designed cloak can be realized by subwavelength dielectric channels enclosed with metallic plates and a uniform dielectric restoring core in air, i.e., no metamaterials or waveguide structures are required. Different from previous studies, the electromagnetic parameters of the designed cloak in this study are strict in accordance with transformation optics (no simplifications), which can achieve a nearly perfect omnidirectional cloaking effect at the design frequency by natural materials. Due to the transformation-invariant feature of the ONM, the shape, size and position of the concealed region can be adjusted freely, while the material parameters of the corresponding cloak remain unchanged.